Accreditation of Accounting Curriculums. - Allyn, Robert G. (The Accounting Review, 1966)
Abstract The article focuses on various aspects of accreditation of accounting curriculums and certified public accountant examination in the U.S. Referring to the standard reference book on higher education American Universities and Colleges, one find that accreditation is understood to comprise four stages including establishment of standards of criteria, inspection by competent authorities to determine whether an institution meets the established criteria, publication of a list of institutions that conform to the criteria and periodic reviews to ascertain whether accredited institutions continue to meet the criteria. To this framework should be added a recent development, or change in emphasis, that is, the reliance upon a pit-visitation self-analysis. The general trend has been that the accrediting bodies are placing less emphasis upon meeting quantitative standards and more upon voluntary improvement. Through self-analysis an institution is, therefore, able to set in motion steps to improve and meet the standards set up by the accrediting body.